Zu Stellung und Traditionen der Medienlinguistik im polnischen und deutschsprachigen Forschungsraum anhand programmatischer Aufsätze zur Entstehung der Disziplin - BILUT-HOMPLEWICZ, ZOFIA (Stylistyka, 2024)
Even the youngest disciplines of academic research have a history. The emergence of a specific discipline, even the most modern one, like medialinguistics, does not happen in a scholarly vacuum and specific traditions always play an important role there. This article aims to characterise the programme articles of two leading authors dealing with medialinguistics in the Polish- and German-speaking research area, Mediolingwistyka. Theory Methodology. Idea (2014) by Bogusław Skowronek and Hartmut Stöckl’s Zu Status und Methodik eines (noch) emergenten Forschungsfeldes (2012). It is worth noting that Stöckl’s dissertation has been translated into Polish twice and was published in 2015. These articles can undoubtedly be considered representative as they constitute a clear caesura in the development of the new discipline and have become a point of reference for a wide range of researchers. The analysis includes a reflection on the way of referring to various research trends that have had an impact on the constitution of medialinguistics; it also emphasises the relationship between the discipline and the research tradition. It is then interesting to explore the way these authors show the emergence of medialinguistics and how they mark its centres of gravity. It also seems important to refer to certain approaches and methodological assumptions characteristic of both areas.